Differences in rates of tyrosine aminotransferase deinduction with cyclic AMP and glucocorticoids. - Lewis, E J (1982)
As an indirect test of the possibility that cyclic AMP produces its stimulatory effects on the synthesis of tyrosine aminotransferase (L-tyrosine:2-oxoglutarate aminotransferase, EC 2.6.1.5) by stabilizing its mRNA, the kinetics of decline in the rate of synthesis of this enzyme was measured in rat hepatoma cells following inducer removal or addition of RNA synthesis inhibitors. In all cases in which cells were previously exposed to cyclic AMP, the decline in enzyme synthesis after removal of inducer or addition of inhibitors of RNA synthesis was 4 to 5 times more rapid than in cells exposed to a glucocorticoid (dexamethasone) which also induces the aminotransferase. Thus, it seems unlikely that cyclic AMP had been acting by stabilizing the mRNA that directs the synthesis of the aminotransferase. Possible explanations for these paradoxical results are suggested. A more rapid decline in enzyme synthesis was also seen in cells induced with both cyclic AMP and glucocorticoid, suggesting direct interaction between the two inducers.